UNIT 7.14 ELISPOT Assay for Measurement of Antigen‐Specific and Polyclonal Antibody Responses. (2nd February 2015) - Lycke, Nils; Coico, Richard
Abstract : The enzyme‐linked immunospot (ELISPOT) assay for detection of antigen‐specific and polyclonal antibody responses by single antibody‐secreting cells has become the method of choice due to its cell‐based quantitative value. Antigen stability and specificity and the diversity of antigens that can be used in the assay have contributed to the translational application of ELISPOT as demonstrated by many FDA‐approved clinical tests that employ this technique. In addition, the ELISPOT assay can be used to detect two antigenically different secreted antibodies simultaneously by two‐color analysis and offers the unique possibility of quantifying the number of antibody molecules secreted per cell. © 2015 by John Wiley & Sons, Inc.